2023
DOI: 10.3390/healthcare11060820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise and Physical Activity Levels on Childhood Cancer: An Umbrella Review

Abstract: Patients and survivors of childhood cancer experience adverse effects related to the disease and its treatment. These adverse effects are associated with both physiological and psychological health. Exercise helps manage the side effects and improve the health outcomes. The objective of this umbrella review is to search the current literature in the context of exercise and physical activity as complementary interventions on pediatric cancer and to provide comprehensive information about the derived health outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…Previous studies have reported that most children with cancer experience a decline in exercise tolerability during treatment, resulting in low HRQOL, 11,16,25 and they often refuse PT due to various reasons, including fatigue. 19,27 In this study, the rate of early PT implementation was high, and no adverse events were observed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have reported that most children with cancer experience a decline in exercise tolerability during treatment, resulting in low HRQOL, 11,16,25 and they often refuse PT due to various reasons, including fatigue. 19,27 In this study, the rate of early PT implementation was high, and no adverse events were observed.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that exercise training has a positive effect on physical fitness among childhood cancer survivors. [7][8][9][10][11][12][13][14][15][16] High-intensity exercise after treatment is associated with a lower psychological burden and cognitive impairment in childhood cancer survivors. 30 Our study showed that controlled, relatively low-intensity exercise under the guidance of a physical therapist improved HRQOL during intensive cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations